PENGEMBANGAN MEDIA KARTU PINTAR (KATAR) PADA MATA PELAJARAN MATEMATIKA MATERI PERKALIAN BAGI SISWA KELAS II SD - Purwaningtyas, Alyshia Herny; Mardati, Asih (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
This study aims to determine the steps of the development and quality of smart card media (KATAR) in Mathematics subject matter multiplication.This research using ADDIE model with 5 stages: analyze, design, develop, implement, evaluate. The trial subjects in this study were 19 students in grade II and teachers in Sidomulyo 1 Salaman Elementary School. Data collection techniques in the form of interviews, observation and questionnaires. Data analysis used qualitative data analysis and quantitative data analysis. The result showed that the smart card media (KATAR) was appropriate to be used with a score of 95 (Good) from the media expert validator, 45 (Good) from the material expert validator, 43 (Very Good) from the learning expert validator. The results of student responses in small- scale trials get a score of 60 with a percentage of 100 (Very Good) and in large-scaletrials get a score of 130 with a percentage of 100(Very Good). Students respond that learning to use smart card media (KATAR) is fun andcan be learned while playing and the material learned is easy to understand.